The Study Of Fiscal Sustainability For The Case Of Overindebted European Countries - Andreea STOIAN (Financial Studies, 2012)
This study aims in analysing the fiscal sustainability for the case of European countries most affected by the economic downturn and sovereign debt: Portugal, Ireland, Italy, Greece and Spain. For that purpose, we apply fiscal reaction function which indicates the speed and the size of government response to shocks on public debt. We use annual data ranged on 1995-2013. The results show that only for the cases of Italy and Portugal governments managed to fulfil the conditions for a sustainable fiscal policy. For these countries, the response is positive and immediate. On contrary, for Ireland we detect a negative reaction in the sense of a decreasing primary surplus to the increase of public debt by 1 p.p.. For the cases of Greece and Spain, the results are not statistically significant and we cannot conclude whether fiscal policy is sustainable or not. But we can emphasize a positive reaction to the increase of public debt cost in the case of Spain.